LGBTQ+ Collegiate Athletes and the Double Bind: Insights From the Experiences of Out Varsity Athletes - Evan Brody; D. Travers Scott; Katrina L. Pariera (International Journal of Communication, 2022)
This article presents recommendations for supporting out LGBTQ+ collegiate varsity athletes based on self-descriptions of their experiences. Within a larger quantitative survey, 63 former and current varsity athletes, who were out as LGBTQ+ while competing, wrote about their experiences. We then thematically analyzed their responses. Participants describe a double bind in which they desire more specific support for their unique LGBTQ+ identity at an institutional level yet request that athletic programs not spectacularize that difference at an individual level. Athletes suggest that programs signal their support of LGBTQ+ athletes more proactively and through the use of safe zones, increased educational opportunities for allies, and more visible and vocal pro-LGBTQ+ stances from those in leadership positions. Practical implications, such as an LGBTQ+-conscious approach to supporting athletes, are discussed.